Analisis Indeks Keberlanjutan Pengelolaan Sampah Pasar Kebayoran Lama - Shafira, Rizka; Astharini, Dwi; Noriko, Nita (JURNAL TEKNOSAINS KODEPENA, 2025)
Waste management in traditional markets is a major challenge in the context of urbanization and environmental sustainability. This study aims to analyze the sustainability index of waste management in Pasar Kebayoran Lama, Jakarta, using a three-dimensional approach: ecological, social, and economic. The methods used are literature study and assessment simulation based on indicators relevant to national policies, such as Law No. 18 Year 2008. The analysis showed that the overall sustainability index score was 1.5, indicating unsustainable conditions. The ecological aspect scored 1.3, social 1.6, and economic 1.6, reflecting the low effectiveness of waste management, lack of community participation, and not optimal waste-based economic empowerment. The proposed action plan includes increased education, waste segregation and recycling, and the development of a circular economy model. This study recommends cross-sector collaboration and continuous monitoring to realize a more ethical, efficient, and sustainable market waste management.